2008
DOI: 10.1007/s11071-008-9458-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the slope discontinuities in large deformation finite element formulations

Abstract: In many multibody system applications, the system components are made of structural elements that can have different orientations, leading to slope discontinuities. In this paper, a numerical investigation of a new procedure that can be used to model structures with slope discontinuities in the finite element absolute nodal coordinate formulation (ANCF) is presented. This procedure can be applied to model slope discontinuities in the case of commutative rotations of gradient deficient elements that are used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this paper a planar gradient deficient [25] Euler-Bernoulli beam element is used [30][31][32], Fig. 1.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this paper a planar gradient deficient [25] Euler-Bernoulli beam element is used [30][31][32], Fig. 1.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, the use of gradient vectors instead of rotational angles as nodal variables poses a significant challenge to such applications. For slope discontinuity problems, Shabana et al [13][14][15] demonstrated that a constant linear transformation of slope variables can be performed using body coordinate system or intermediate coordinate system. The transformation which is valid for linear connectivity conditions in cases like spherical hinges and rigid joints does not introduce additional constraint equations during the process of element assembly.…”
Section: Introductionmentioning
confidence: 99%